(untitled) (AYUSHDHARA, 2025)
Ayurveda, the ancient traditional Indian system of medicine, provides a holistic approach to mental health and wellness. The current form of Ayurvedic Psychiatry today consists of Ayurvediya Manas Roga Vigyana, which deals with a wide range of treatment of psychological disorders. Depression is a frequent mental health condition that leads to a persistently low mood or loss of pleasure or lack of interest in daily activities for a long period. The WHO estimates that 350 million individuals worldwide suffer from depression. In Ayurveda, two disorders that closely resemble depression are Vishada and Avsada. People today are restless and have varied degrees of anxiety disorders due to modern lifestyle and eating habits, overwhelming pressure to reach goals in less time, and unhealthy social lives. Acharya Charak asserts that deliberate disobedience is the cause of all psychological issues and illness. Emotions that humans experience include jealousy, misery, fright, rage, selfishness, hatred, and others. Pragya Apradha is the cause of all psychiatric diseases. For dealing with Anxiety and Depression, there are many ways mentioned in our classics, such as Medhya Rasayana, Dhyan, Yog Dincharya, Ratricharya, Achara Rasayan, and Panchakarma procedures like Shirodhara, Abhyanga, etc.